Particle control for semiconductor manufacturing - Donovan, R.P (Marcel Dekker, 1990)
The trend toward chip designs of ever-decreasing dimensions promises increased importance for particle control partices. "Particle control for semiconductor manufacturing" focuses on submicrometer contaminants that introduce unwanted, unmodeled effected in device performance.